Raman microscopy as a defect microprobe for hydrogen bonding characterization in materials used in fusion applications. Issue 1 (29th October 2014) - Pardanaud, Cédric; Addab, Younès; Martin, Céline; Roubin, Pascale; Pegourié, Bernard; Oberkofler, Martin; Köppen, Martin; Dittmar, Timo; Linsmeier, Christian
Abstract We present the Raman microscopy ability to detect and characterize the way hydrogen is bonded with elements that will be used for ITER's plasma facing components. For this purpose we first use hydrogenated amorphous carbon samples, formed subsequently to plasma‐wall interactions (hydrogen implantation, erosion, deposition...) occurring inside tokamaks, to demonstrate how this technique can be used to retrieve useful information. We pay attention in identifying which spectroscopic parameters are sensitive to the local structure (sp3/sp2) and which gives information on the hydrogen content using isothermal and linear temperature ramp studies on reference samples produced by plasma enhanced chemical vapor deposition. We then focus on the possibility to use this fast, non‐destructive and non‐contact technique to characterize the influence of hydrogen isotope implantation in few nanometers of graphite and beryllium as C is still used in the JT‐60 tokamak and Be is used in JET and will be used as plasma‐facing component in the future reactor ITER. We also pay attention on implantation in tungsten oxide which may be formed accidently in the machine. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)